Association of the cyclooxygenase-2 1759A allele with migraine in Chinese Han individuals - Guan, Xinying (PLoS One, 2020)
Cyclooxygenase-2 (COX-2) is known to be involved in the pathogenesis of migraine, and some polymorphisms are known to affect the expression of COX-2. This retrospective case-control study aimed to explore the associations between the -765 G>C (rs20417), -1759 G>A (rs3218625), and -8473 C>T (rs5275) COX-2 polymorphisms and migraine in Chinese Han individuals. One hundred and ten unrelated Han Chinese patients with migraine and 108 healthy controls were recruited between 03/2014 and 08/2016 at the First Affiliated Hospital of Nanjing Medical University and the First People's Hospital of Lianyungang City. The genotypes of all polymorphisms in controls followed the Hardy-Weinberg equilibrium (P = 0.215, P = 0.884, and P = 0.689). There were differences in the genotype and allele distributions of the COX-2-1759G>A (Gly587Arg) polymorphism between the migraine and control groups (P = 0.038 and P = 0.040, respectively). Compared with the COX-2-1759AG genotype, GG genotype carriers had an increased risk of migraine (odds ratio (OR) = 8.720, 95% confidence interval (CI): 1.072–70.960, P = 0.038). The frequency of the COX-2-1759A allele in patients with migraine was significantly lower than the controls (OR = 0.119, 95%CI: 0.015–0.957, P = 0.040). Adjusted age and sex, a statistical difference was found in the dominant model of COX-2-1759 G>A (OR = 0.118, 95% CI 0.014 to 0.962, P = 0.046). No significant difference was detected regarding the -765G>C and -8473T>C polymorphisms between the two groups. The COX-2 1759A allele might be involved in the development of migraine in Chinese Han individuals, but this will have to be confirmed in large-scale studies.